Analisis Hotspot (Getis Ord Gi*) Pola Spasial Frekuensi Kecelakaan Lalu Lintas di Kota Balikpapan - Simanungkalit, Maylani Angelina; Hidayat, Arief; Nugroho, Rizky Arif; Depari, Andi Sahputra (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2024)
Transportation is a major element in urban and economic development, but the rapid growth of transportation and the complexity of its problems create an urgent need for effective solutions, especially regarding significant traffic accidents in Indonesia, including in Balikpapan City. This study aims to analyze the spatial pattern of traffic accidents in Balikpapan using the Getis-Ord Gi* method to identify areas with high (hotspot) and low (coldspot) accident frequency. Secondary data from various sources are used in this analysis. By spatial modeling using ArcGIS, the results show that the highest accident hotspots are located in the sub-districts of North Balikpapan West, Balikpapan City, Central Balikpapan, and South Balikpapan. The findings are expected to help in designing more effective accident prevention strategies to improve road safety in Balikpapan City. Keywords: ArcGIS, traffic accident, Getis-Ord Gi*, hotspot, spatial pattern.